Pakistan - Sonneborn, Liz (2013)
Readers will learn about the area's entire history, from its earliest civilizations to its place in the modern world. They will also discover the rich cultural heritage of Pakistan's people and the varied landscapes and wildlife of its natural environments.
Ancient city, modern nation -- High and dry -- Into the wild -- Past and present -- Governing Pakistan -- Making a living -- The Pakistani people -- A Muslim nation -- Cultural life -- The Pakistani way.
Includes bibliographical references (page 134) and index.
1060L
Accelerated Reader AR
Keywords: Pakistan -- Juvenile literature